Louisa the extraordinary life of Mrs. Adams - Thomas, Louisa (Penguin Press, 2016)
An intimate portrait of Louisa Catherine Adams, the wife of John Quincy Adams, who witnessed firsthand the greatest transformations of her time
Includes bibliographical references and index
Keywords: Adams, John Quincy / 1767-1848; Adams, Louisa Catherine / 1775-1852; Adams, Louisa Catherine -- 1775-1852; Adams, John Quincy -- 1767-1848; Adams, John Quincy; Adams, Louisa Catherine; Biography; Biographies; Presidents' spouses; Presidents' spouses -- United States -- Biography; United States; USA; Biografie